Colonization patterns of benthic macroinvertebrates in fertilized and non-fertilized earthen fish ponds - Patrick O Orwa; Reuben Omondi; Emily J Chemoiwa (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2018)
Study conducted in Kwanza, Trans-Nzoia County to determine the colonization pattern of benthic macroinvertebrates in earthen fish ponds. This was done to ascertain the right stocking time of ponds when the natural fish food is in plenty. Two ponds were used for this study; one was treated with organic manure while the other was not fertilized. Sampling for physico-chemical parameters were then taken immediately after filling the ponds and repeated weekly for six weeks while benthic macroinvertebrates were first sampled after week 1 and repeated weekly for six weeks. The results obtained were compared between the two treatments and per treatment over time. There were significant differences in most parameters over the weeks and between the treatments. Attainment of suitable conditions for stocking was however at week 3 for fertilized and week 4 for the non-fertilized contrary to the usual two week period advised by most procedures.